Artificial Intelligence in Liver Diseases: Recent Advances - Lu, Feifei; Meng, Yao; Song, Xiaoting; Li, Xiaotong; Liu, Zhuang; Gu, Chunru; Zheng, Xiaojie; Jing, Yi; Cai, Wei; Pinyopornpanish, Kanokwan; Mancuso, Andrea; Romeiro, Fernando Gomes [UNESP]; et al. (Springer Nature, 2024)
Liver diseases cause a significant burden on public health worldwide. In spite of great advances during recent years, there are still many challenges in the diagnosis and treatment of liver diseases. During recent years, artificial intelligence (AI) has been widely used for the diagnosis, risk stratification, and prognostic prediction of various diseases based on clinical datasets and medical images. Accumulative studies have shown its performance for diagnosing patients with nonalcoholic fatty liver disease and liver fibrosis and assessing their severity, and for predicting treatment response and recurrence of hepatocellular carcinoma, outcomes of liver transplantation recipients, and risk of drug-induced liver injury. Herein, we aim to comprehensively summarize the current evidence regarding diagnostic, prognostic, and/or therapeutic role of AI in these common liver diseases.
Keywords: Artificial intelligence; Cirrhosis; Deep learning; Fibrosis; Hepatic; Liver disease; Machine learning